Lessons Learned: Providing Supportive Accountability in an Online Anxiety Intervention. Issue 3 (May 2022) - Werntz, Alexandra; Silverman, Alexandra L.; Behan, Henry; Patel, Suraj K.; Beltzer, Miranda; Boukhechba, Mehdi O.; Barnes, Laura; Teachman, Bethany A.
Highlights: The use of technology-delivered interventions can be supported by telecoaching. Some users of an anxiety intervention may be reluctant to interact with a coach. Telecoaching protocols should be flexible to meet the needs of intervention users. Abstract: Technology-delivered interventions have the potential to help address the treatment gap in mental health care but are plagued by high attrition. Adding coaching, or minimal contact with a nonspecialist provider, may encourage engagement and decrease dropout, while remaining scalable. Coaching has been studied in interventions for various mental health conditions but has not yet been tested with anxious samples. This study describes the development of and reactions to a low-intensity coaching protocol administered to N = 282 anxious adults identified as high risk to drop out of a web-based cognitive bias modification for interpretation intervention. Undergraduate research assistants were trained as coaches and communicated with participants via phone calls and synchronous text messaging. About half of the sample never responded to coaches' attempts to schedule an initial phone call or did not answer the call, though about 30% completed the full intervention with their coach. Some anxious adults may choose technology-delivered interventions specifically for their lack of human contact and may fear talking to strangers on the phone; future recommendations include taking a more intensive user-centered design approach to creating and implementing a coaching protocol, allowing coaching support to be optional, and providing users with more information about how and why the intervention works.